Differences in instructional quality during the Covid-19 pandemic between Oman and Germany and the role of teacher competences - Ohle-Peters, Annika; Shahat, Mohamed A. (Frontiers in Education, 2023)
Introduction School closures during the Covid-19 pandemic hit educational systems worldwide, forcing teachers to switch to digital learning settings. The presented study aims to (a) adapt and evaluate scales on instructional quality in digital settings, (b) describe instructional quality during the pandemic, and (c) to identify predictive teacher competences. Method Data was assessed in a cross-sectional design via an online questionnaire conducted in Oman and Germany simultaneously. Results Analyses of data from N = 284 teachers in Oman and Germany revealed mostly good psychometric parameters, differences in instructional quality between both countries, and positive relations between teachers’ competences and instructional quality. Conclusion The present study contributes to instrument development and to the growing body of research, investigating teaching quality during the pandemic.